Pengaruh Perilaku Konsumen terhadap Pengambilan Keputusan dalam Menentukan Destinasi Wisata di Kabupaten Hulu Sungai Tengah - Marliani, Gusti; Sugiarto, Toto (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2019)
The purpose of this study is to analyze the influence of consumer behavior on their decision making both partially and simultaneously in determining the Tourism Destination to Hulu Sungai Tengah District. The results of this study can provide input for stakeholders in decision making to advance tourism in Hulu Sungai Tengah, in this case, can help increase the number of tourist visits in Hulu Sungai Tengah.. Simultaneously / thoroughly independent variables which include Cultural Factor Variables (X1), Social Factor Variables (X2), Personal Factor Variables (X3), and Psychological Factor Variables (X4) simultaneously have a significant effect on consumer decision making in determining Tourism Visits (Y ) in Hulu Sungai Tengah Regency. The test results show that F count is greater than F table (F count = 267,457> F table = 3.81). Adjusted R Square equal to 0.965, which means that the independent variable has a contribution variance of 96.5% to the dependent variable, while the remaining 3.5% is given by other variables not included in this study.